Using of proton beam writing techniques for fabrication of micro difraction gratings - Ponomarev, A.G.; Kolinko, S.V.; Rebrov, V.A.; Kolomiets, V.N.; Kravchenko, S.N. (Вопросы атомной науки и техники, 2018)
To obtain micrometric gratings with a high aspect ratio by lithographic technique, it is proposed to use a proton beam focused in a line and electromagnetic scanning in the transverse direction to irradiate the resistive material. Numerical modeling is carried out to optimize the parameters of the probe forming system for this task. The calculations were confirmed during the experimental implementation of the proposed technique. A grating from the 23.4×2060 μm lines was made. Для виробництва мікродифракційних граток з великим аспектним співвідношенням методом літографії запропоновано застосувати для опромінення фоторезисту протонний пучок, сфокусований в лінію, та електромагнітне сканування в поперечному напрямку. Проведене чисельне моделювання з оптимізації параметрів ЗФС для даної задачі. Розрахунки підтверджено при експериментальній реалізації запропонованого методу, виготовлено гратку зi смугами розмірами 23,4×2060 мкм. Для получения микродифракционных решеток с высоким аспектным соотношением методом литографии предложено использовать для облучения фоторезиста протонный пучок, сфокусированный в линию, и электромагнитное сканирование в поперечном направлении. Проведено численное моделирование по оптимизации параметров ЗФС для данной задачи. Расчеты подтверждены при экспериментальной реализации предложенного метода, получена решетка из полос размерами 23,4×2060 мкм.